Densidade e produtividade da madeira de híbrido e seminal de Pinus caribaea - Rezende, Marcos Antonio De [UNESP] (2023)
The objective this study was a comparative evaluation of wood density and productivity of five treatments of hybrids of Pinus caribaea var. hondurensis x P. tecunumannii with a seminal of P. caribaea var. hondurensis planted in the same settlement in the town of Agudos-SP. It was determined the basic density of each disc by the immersion method. The productivity was determined by the average annual increments volume and mass. Results showed that the hybrids treatments had productivity in volume of up to 23% higher what the seminal treatment, however had a decrease of approximately 10% in density.